The “Left-hand strategy” for design, synthesis and discovery of novel triazole-mercaptobenzothiazole hybrid compounds as potent quorum sensing inhibitors and anti-biofilm formation of Pseudomonas aeruginosa - Truong, Thanh Tung (New Journal of Chemistry, 2022)
45, 21631-21637